Marketing Educational Services : The Practices Of Marketing Mix in Building Brand Image Of SMK Bina Mandiri Multimedia Bogor - Usman, Usman; Giyoto, Giyoto; Mulyadi, Didi (Publisher Cv. Inara, 2023)
This article discusses the marketing of educational services; The application of marketing mix in building branding image at SMK Bina Mandiri Multimedia includes four main elements, namely product, price, promotion, and distribution. This research is a qualitative study where data is obtained through interviews, documentation and observation of all parties involved in this marketing process consisting of the Foundation, Principal and field marketing personnel who make visits to schools. The results showed that in terms of products, SMK Bina Mandiri Multimedia needs to present quality education programs that are relevant to the needs of the multimedia industry. This may include developing an up-to-date curriculum, upgrading facilities and equipment, and ensuring optimal teaching and learning quality. Pricing should consider the added value offered by SMK Bina Mandiri Multimedia. Fair and competitive pricing can attract prospective students and illustrate the quality of education offered by the school. Promotion should be done effectively to introduce and strengthen the brand image of SMK Bina Mandiri Multimedia. Marketing strategies such as advertising, promotional activities, and social media utilization can be used to increase visibility and attract prospective students and parents. Distribution relates to the way SMK Bina Mandiri Multimedia conveys information regarding their educational programs. This may involve cooperation with other educational institutions, participation in education fairs, or utilization of online platforms to connect with potential students. In general, the strategy carried out by SMK Bina Mandiri Multi Media has been quite successful, which can be seen from the SMK Bina Mandiri Multi Media brand which is already quite well known in this area with the number of registrations reaching more than 250 each year. However, in anticipation of increasingly fierce competition, the marketing strategy must always adjust to the changing characteristics of consumers.